Optimizing nitrogen, phosphorus, and potassium requirements to improve Origanum dubium Boiss. growth, nutrient and water use efficiency, essential oil yield and composition - Chrysargyris, Antonios; Tzortzakis, Nikos G. (My University, 2025)
Medicinal and aromatic plant production is popular in the agricultural sector because of the phytochemical compounds that have a powerful effect on people health. The present study examined the impacts of various nitrogen (N: 75, 150, and 300 mg/L), phosphorus (P: 50, 75, and 100 mg/L), and potassium (K: 150, 350, and 550 mg/L) concentration in the nutrient solution (NS) on growth, physiological attributes, antioxidant capacity, nutrient accumulation and essential oil (EO) components in Origanum dubium plants grown in hydroponics. The NPK levels of 150 mg N/L, 75 mg P/L and 350 mg K/L in the NS, an intermediate fertilization scheme, revealed increased K content in the plant tissue. O. dubium grown in N75 levels indicated increased total phenols and antioxidant capacity, increased P, Na, and Cu content, increased water use efficiency and the highest p-cymene content in the EO. In contrast, the N300 levels in the NS, increased N accumulation and total flavonoids in plants, but decreased the main EO component, carvacrol. The K150 levels in the NS decreased plant biomass and caused oxidative stress, indicated by the higher lipid peroxidation, and the acceleration of the terpene's synthesis with the raised carvacrol content. The K550 levels mirrored the highest nutrient use efficiency in plants while the P100 levels impacted the leaf chlorophylls and manganese content. The raise N, P, K in the NS increased mineral accumulation in the plants. Plant biomass and EO yield were not differed by the various N or P levels in the NS. Therefore, tailoring the NS composition in hydroponic cultivation of O. dubium, may supply plant biomass and EO of specific composition, such EO-enriched in carvacrol by the K150 levels in the NS or EO-enriched in p-cymene by the N75 levels in the NS, addressing industry demands.
Keywords: Antioxidants; Macronutrients; Mineral fertilizer; Origanum spp.; Soilless culture